Special theory of relativity: a view of an external observer - I. O. Sazonenko; V. I. Sazonenko (Литьë и металлургия, 2020)
Based on the generally accepted presentation of the ideas of the private theory of relativity, examples of relative simultaneity and superluminal speed are considered. A variant of the ban on travel to the past in inertial reference systems is proposed.